Nutrition education and changes in mother's behavior towards fulfillment of vegetable and fruit consumption strategies in preschool children - Rapitos Sidiq; Rina Hasniyati; Marni Handayani (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2021)
The nutritional needs of preschool children are very important for their growth and development. However, the problem is the low consumption of preschool children for fruits and vegetables, so it requires special strategies, for that the role of the family is very important. This study aims to determine the impact of nutrition education and changes in mother's behavior towards the fulfillment of vegetable and fruit consumption strategies in pre-school children. This research uses quasi-experimental and observational methods, observations were carried out on 30 September 2019 on 44 preschool children. Data collection was carried out on September 20, 2019, in Early Childhood Education SB in 50 mothers of preschool children. The data is processed in stages; editing, coding, transferring and tabulating. Univariate data analysis in the form of frequency distribution tables, paired t-test statistical test. The results showed an average value of knowledge before the intervention (p= 0,000). Observation results show that after nutrition education was given, only 31,8% of preschool children were given vegetable and fruit supplies or processed food vegetables and fruits by the mother when going to school. The conclusion of the study is nutrition education on maternal strategies in increasing consumption of vegetables and fruit in preschool children in early childhood education effectively changing maternal knowledge but has not had a comprehensive impact on changes in mother’s behavior